Strategies for using educational technology in university teaching - laadjal, Afifa (Journal of Social Sciences and Humanities, 2021)
The study aims to clarify that university teaching today needs more new strategies and educational methods that provide us with wide and varied educational horizons to develop skills, creativity and production in teaching, as it represents a purposeful and planned human activity that is implemented in a way that is the positive interaction between the teacher and the learner and The subject of learning and its environment, which leads to the growth of the knowledge side. Strategies for using educational technology in university teaching help to communicate and open up to the other and provide competitive learning in addition to developing communication and interaction skills of the professor and the student.